2020
DOI: 10.16966/2380-5544.152
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control, Medication Use and Obesity among Patients with Type 2 Diabetes Mellitus Presenting to an Endocrinology Clinic during the War in Yemen. A Three-Year Retrospective Study

Abstract: Background and Aims: The war in Yemen caused the already weak health system in the country to decline. We conducted a 3-year retrospective chart review on patients with type 2 Diabetes Mellitus (DM) attending an endocrinology center for the first time during the war, most of the patients were treated by internists and in government hospitals prior to presentation and only a small amount had seen a specialist prior to presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…3 A case report from a Cameroon refugee camp also supported our nding demonstrating insecurity increased the rate of severe acute malnutrition among patient with type-1 DM 14 . In contrast to our study, a study from Yemen reported that 74.7% followed diabetic diet and 98% of the patients didn't change their dietary habits 11 .…”
Section: Discussioncontrasting
confidence: 99%
“…3 A case report from a Cameroon refugee camp also supported our nding demonstrating insecurity increased the rate of severe acute malnutrition among patient with type-1 DM 14 . In contrast to our study, a study from Yemen reported that 74.7% followed diabetic diet and 98% of the patients didn't change their dietary habits 11 .…”
Section: Discussioncontrasting
confidence: 99%